RARE-01. NATIONWIDE TRENDS IN MANAGEMENT OF ADULT MYXOPAPILLARY EPENDYMOMA. (11th November 2019) - Baracena, Daphne; Kelly, Patrick; Khudanyan, Arpine; Turina, Claire; Jaboin, Jerry; McClelland III, Shearwood
Abstract: INTRODUCTION: Myxopapillary ependymomas (MPE) are WHO Grade I ependymomas that occur in the spine and have an annual incidence of 0.05–0.08 per 100, 000 people. Maximal, safe surgical resection is the recommended first line therapy. Due to the rarity of the disease there is a relatively poor understanding of the use of radiotherapy (RT) in the management of disease. METHODS: Using the National Cancer Database (NCDB), we analyzed the patterns and impact of RT on spinal MPE in adults diagnosed between 2002 and 2016. RESULTS: Of 753 qualifying cases, the majority of patients underwent resection (n = 617, 81.9%). A relatively small portion received RT (n = 103, 13.3%) with most receiving RT after surgical resection (n = 98, 95.1%). The likelihood of patients to undergo resection and RT was significantly associated with patient age at diagnosis (p = 0.002), tumor size (p < 0.001), and race (p = 0.017). Chemotherapy was not widely utilized (only 0.27% of patients). DISCUSSION: Although practice patterns can be highlighted from this 15-year analysis, given the high survival in this disease entity, progression-free survival (PFS) is an important outcome not available from this database. As expected, surgery is the primary means to manage adult MPE. For spinal MPE, it is understood that gross total resection (GTR) should be attempted whenever possible as GTR has been associated with improved PFS in several studies. RT and chemotherapy are used infrequently. In univariate analyses, RT was employed more often for larger tumor sizes, Latino/Hispanic ethnicity, and younger age at diagnosis. The impact of RT on overall survival is indeterminate given the 1.6% death rate in the cohort. Analyses of the impact of RT on PFS in a larger database would be beneficial for determining an algorithm for post-operative and definitive radiotherapy in this disease entity.